Ostension, inference and response: analysing participant moves in Community Interpreting dialogues - Mason, Ian (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Following a review of the methods employed in some recent studies, this paper proposes a wayforwardfor pragmatics-sensitive research into actual participant moves in community interpreting events. Its aim is to overcome some of the objections that have been raised to methods in critical discourse analysis, conversation analysis and pragmatics and to relate microlevel analysis of participants’ utterances to the broader issues of role, power distribution, norms and so on that have dominated discussion of interpreter-mediated communication. Adopting a broadly ostensive-inferential view of communication, we examine the nature of the evidence that can be adduced in support of causal models and suggest that it is to be found in the real-time responses of the participants themselves to each other ’s moves rather than in analysts’ imagined reconstruction of context, intentionality and acceptability.